School closures and prescription medication use among children and adolescents before and during the COVID-19 pandemic in the USA, 2019-2022 - Dima M Qato; Andrew Shooshtari; Abeeha Mirza (BMJ Publishing Group, 2024)
The impact of schools closing for in-person instruction in the USA during the COVID-19 pandemic on the use of prescription medications is not known. In this study, we examined changes in the total prescriptions filled, specifically for attention deficit hyperactivity disorder (ADHD) medications, among school-aged children and adolescents aged 10-19 years during periods before and after complete school closures between October 2019 and September 2022. Our findings indicate that complete school closures were associated with declines in the use of ADHD medications among younger populations in the USA. These findings suggest that the underuse of ADHD medications may be an overlooked contributor to declines in academic performance observed during periods of school closures during the COVID-19 pandemic.